Knowledge Management in Rural Community to Reach Sustainable Village Development - Luthfiana, Ainul (Prosiding Seminar, 2023)
Rural communities have better natural resources than urban areas, but there is development gap so the villages still underneath cities. Optimizing natural resources to improve the rural communities standard living requires the role key of human resources who are competent and have strong moral values ​​to uphold the principles of sustainable development. The customs and culture of the community have local wisdom values ​​which are an intellectual asset for the village community to be used as a fulcrum in developing a village with a distinctive character as well as a mission to maintain its sustainability. The problem that occurs is that there is no qualified space in managing tacit into explicit knowledge assets so that they can be utilized appropriately by village stakeholders. This paper conducts a literature review to examine and understand how knowledge management applied in village communities to reach sustainable village development